2014
DOI: 10.1371/journal.pone.0097135
|View full text |Cite
|
Sign up to set email alerts
|

Short Daily versus Conventional Hemodialysis for Hypertensive Patients: A Randomized Cross-Over Study

Abstract: BackgroundTreatment of end stage renal disease patients with short daily hemodialysis has been associated with an improvement in blood pressure. It is unclear from these studies if anti-hypertensive management had been optimized prior to starting short daily hemodialysis. Also, the potential mechanism(s) of blood pressure improvement remain to be fully elucidated.Study Design, Setting and ParticipantsWe undertook a randomized cross-over trial in adult hypertensive patients with ESRD treated with conventional h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…noted that EAT may be an early predictor of endothelial dysfunction and a precursor of the inflammation that causes coronary arterial disease . General increase in inflammatory markers (including IL‐6) may occur due to some mechanisms including volume overload, and oxidative stress . ESRD patients with volume overload evaluated in a bioimpedance study in the literature revealed that hypervolemia was associated with the markers of malnutrition, inflammation and atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…noted that EAT may be an early predictor of endothelial dysfunction and a precursor of the inflammation that causes coronary arterial disease . General increase in inflammatory markers (including IL‐6) may occur due to some mechanisms including volume overload, and oxidative stress . ESRD patients with volume overload evaluated in a bioimpedance study in the literature revealed that hypervolemia was associated with the markers of malnutrition, inflammation and atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…Frequent HD had significantly greater reductions in pre-HD systolic BP and number of antihypertensive medications used. A significant reduction in left ventricular (LV) mass is found with frequent HD [21] [22].…”
Section: Discussionmentioning
confidence: 99%
“…[7], [28], [29], [30], [31] that can cause to the loss of renal function [7]. Also, some mechanisms including volume overload and oxidative stress can cause the usual increase in inflammatory symptoms (including IL-6) [32].…”
Section: Discussionmentioning
confidence: 99%